IMPROVING GRAMMAR SKILL USING EGRA TECHNIQUE FOR THE STUDENTS’ EIGHTH GRADE AT SMPN 5 CIMAHI - Mayang Kusumastuti; Mega Pratiwi; Hendra Husnussalam (IKIP Siliwangi, 2019)
Grammar is one part to improve four skills that we also known. To enhance grammar skill we have to prefer the accurately method as a way in studying grammar. The researcher was chosen Exposure, Generalization, Reinforcement, and Application (EGRA) technique as a method to teaching English grammar to students’ eigtht grade at SMPN 5 Cimahi. It was arranged with using pre-experimental method, peculiarly one-group pre-test post-test design. The technique showed that can develop grammar skill students’. The average score of the test result is 40,83 for the pre-test and 71,70 for the post-test. From the result, it can determine that EGRA technique can improve grammar skill students’. Besides that, EGRA technique can build a good team work in the classroom.